2022
DOI: 10.1364/oe.452665
|View full text |Cite
|
Sign up to set email alerts
|

Biological SERS-active sensor platform based on flexible silk fibroin film and gold nanoislands

Abstract: In contrast to conventional surface-enhanced Raman scattering (SERS) platforms implemented on non-biological substrates, silk fibroin has the unique advantages of long-term biosafety and controllable biodegradability for in vitro and in vivo biomedical applications, as well as flexibility and process-compatibility. In this study, a silk fibroin film was developed to fabricate a flexible SERS sensor template with nanogap-rich gold nanoislands. The proposed biological SERS platform presents fairly good enhanceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The nano-islands offer a dense nano-gap structure and excellent spatial uniformity, resulting in sensitive detection. SERS intensity of nano-island was found to be 14 times that of the conventionally used smooth silicon surface, which also improves sensitivity and detection limit [79]. Liu et al reported a Ti 3 C 2 Tx Mxenes and AgNPs-based SERS label-free sensor based on an electrostatic self-assembly method to detect dopamine concentrations of 5-500 µM, as shown in Figure 9a.…”
Section: Sers Sensorsmentioning
confidence: 96%
“…The nano-islands offer a dense nano-gap structure and excellent spatial uniformity, resulting in sensitive detection. SERS intensity of nano-island was found to be 14 times that of the conventionally used smooth silicon surface, which also improves sensitivity and detection limit [79]. Liu et al reported a Ti 3 C 2 Tx Mxenes and AgNPs-based SERS label-free sensor based on an electrostatic self-assembly method to detect dopamine concentrations of 5-500 µM, as shown in Figure 9a.…”
Section: Sers Sensorsmentioning
confidence: 96%
“…Plasmonic structures should be placed on materials with a low Raman signal and should be resistant to the solvents employed to dissolve the test molecule. As depicted in Figure 7 , several materials were evaluated for this purpose in recent years, including graphene [ 88 ], nanowires [ 89 ], silk [ 90 ], paper [ 91 ], and flexible polymers [ 92 ], each of which adds diverse uses to the substrate. These materials enable the creation of SERS substrates that are inexpensive, and expandable for large-scale production.…”
Section: Sers Substrates For Diagnosis At the Point-of-carementioning
confidence: 99%
“…[22] Fibroin is often discussed as substrate material for bioabsorbable electronics or an encapsulation to increase the biocompatibility of implantable devices. [22][23][24][25][26][27] A synthetic, commercially available alternative to fibroin depicts PLA, which is synthesized from starch (e.g., from corn, sugar cane, or potatoes). [28] A reasonable number of biomedical studies deal with PLA as material for medical applications, for example, for tissue engineering, drug carrier systems, cancer therapy, skin and tendon regeneration, orthopaedic and dental devices, surgical tools, and also as substrate material for (bio)sensors.…”
Section: Introductionmentioning
confidence: 99%